THE ROLE OF SMALL-SIDED GAMES IN MODERN SOCCER AND THE ISSUE OF THEIR HOLISM - Miloš Tul; Zdenko Verdenik; Matija Maršič; Matjaž Mulej (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2016)
In the modern soccer, small-sided games (SSG) present a significant proportion of the whole training process. SSG are introduced regularly and with different emphases, depending on the players' basic technical skills and on the training objectives, but also according to different (sports) cultural contexts. SSG immersed into the wider soccer area at different speeds and with different emphases, often with rather modified designs. Due to their extraordinary adaptability and efficiency, SSG as a working method have undergone a great expansion. Their design and (possible) versatility are explained in this paper from a somewhat unusual perspective of the systemic theories as the theories of achieving the greatest possible holism of our reflections and actions. In the foreground of this paper there is the question of SSG integrity (as the prevailing practical methods of work in modern football practice), through the analysis of the conditions required in order to classify the use and further development of SSG in practice as an innovation, taking into account the laws of requisite holism and innovation.